The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fphys.2014.00190
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic, cerebral, and muscle hemodynamic responses during intermittent, isometric contractions of the biceps brachii at three submaximal intensities

Abstract: This study examined the electromyographic, cerebral and muscle hemodynamic responses during intermittent isometric contractions of biceps brachii at 20, 40, and 60% of maximal voluntary contraction (MVC). Eleven volunteers completed 2 min of intermittent isometric contractions (12/min) at an elbow angle of 90° interspersed with 3 min rest between intensities in systematic order. Surface electromyography (EMG) was recorded from the right biceps brachii and near infrared spectroscopy (NIRS) was used to simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Thus, years ago these authors suggested as a possible future direction the association of the muscle oxygenation measurement with other physiological responses monitored during tests and training (for example, HR and blood lactate concentration). Recently, this way has been accomplished and some studies aimed to adopt these recommendations 16,18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, years ago these authors suggested as a possible future direction the association of the muscle oxygenation measurement with other physiological responses monitored during tests and training (for example, HR and blood lactate concentration). Recently, this way has been accomplished and some studies aimed to adopt these recommendations 16,18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the significance of tissue oxygenation 18 there are very few studies investigating the more and less active muscle responses during and after exercise 14,42,[61][62][63] especially in running effort 12,19 . According to Perrey and Ferrari in a recent review 39 , the majority of the NIRS studies examined the responses of the vastus lateralis muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Robertson and Marino [ 11 ] proposed that the prefrontal cortex (PFC) may interpret afferent feedback and play a role in tolerating or terminating fatiguing exercise. During submaximal unilateral contractions, as the intensity of exercise increases, there is an increase in oxygenation of the PFC, as measured by functional near infrared spectroscopy (fNIRS) [ 12 , 13 ]. Generally, increasing the intensity or duration of resistance exercise results in metabolite accumulation which stimulates metaboreceptive muscle afferents.…”
Section: Introductionmentioning
confidence: 99%
“…1 Multimodal studies of muscle function are becoming increasingly common, most of them based on a combination of NIRS and EMG. 18,22,23 Many of these studies focus on investigating the relationship between muscle electrophysiology and oxygenation or hemodynamics [24][25][26][27][28] or on gathering more reliable information on, for example, neuromuscular and metabolic activity in relation to muscle fatigue or injury. 29,30 Moreover, wireless hybrid sEMG/NIRS sensors have recently been proposed for multimodal analysis by such researchers as Guo et al 34 Surface EMG and accelerometer (ACM) have been previously used for example for sign language recognition, 45 fatigue assessment, 46 Parkinson's disease progress assessment 47 and for monitoring daily activities of patients who have had a stroke.…”
mentioning
confidence: 99%